Pengaruh Media Sosial Dan Self Efficacy Terhadap Keputusan Berinvestasi Di Pasar Modal Syariah Melalui Financial Technology - Anggie Angraini; Lemiyana; Oki Sania Riski (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to investigate the influence of Social Media and Self Efficacy on Investment Decisions with Financial Technology as an intervening variable. The population for this research consists of Generation Z individuals in Palembang city who have made investment decisions, with a sample size of 100. Purposive sampling technique was employed to manage the sample, following several procedures. Data analysis was conducted using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with SmartPLS version 4.1. The findings indicate that social media does not influence investment decisions, self efficacy positively affects investment decisions, social media influences financial technology, self efficacy influences financial technology, and financial technology influences investment decisions. In this study, financial technology fully mediates the relationship between social media and investment decisions, while self efficacy partially mediates the relationship between social media and investment decisions.